2023
DOI: 10.3390/ma16083283
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Porous Carbon-Based Non-Precious Metal Electrocatalysts

Abstract: The development of efficient, stable, and economic electrocatalysts are key to the large-scale application of electrochemical energy conversion. Porous carbon-based non-precious metal electrocatalysts are considered to be the most promising materials to replace Pt-based catalysts, which are limited in large-scale applications due to high costs. Because of its high specific surface area and easily regulated structure, a porous carbon matrix is conducive to the dispersion of active sites and mass transfer, showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 218 publications
(264 reference statements)
0
4
0
Order By: Relevance
“…6 Therefore, alternative catalysts, such as nonnoble metal or metal-free catalyst, are necessary. 7,8 Among these alternative catalysts, porous nitrogen-doped carbon materials are emerging. 9 Porous carbon materials can be obtained by carbonization of suited organic polymer-based precursors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Therefore, alternative catalysts, such as nonnoble metal or metal-free catalyst, are necessary. 7,8 Among these alternative catalysts, porous nitrogen-doped carbon materials are emerging. 9 Porous carbon materials can be obtained by carbonization of suited organic polymer-based precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen atoms can be introduced into carbon materials as chemical nitrogen and structural nitrogen. 7,8,24 Both NH x (x: 1-2) and NO x (x: 1-2) can be attributed to chemical nitrogen while pyrrolic N, pyridinic N, and quaternary N belong to structural nitrogen. Chemical nitrogen atoms do not participate in the conjugated π system of graphene/graphite and could be considered as defects in the carbon matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much research in recent years has been focused on metal–nitrogen-doped carbon (M–Nx–C) materials with high activity to investigate the underlying catalysis mechanism due to their clear and conducive structures (M–Nx–C). 12–15 Molecular electrocatalysts with well-defined M–Nx active sites, such as FePc, CoPc, and NiPc, are the primary models for electrocatalysts in studying the structure and activity relationship (SAR). It is widely reported that tuning the electronic structure of the metal in the core of molecular electrocatalysts by altering the structure of the ligand can achieve excellent selectivity for ERCD products.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the self-aggregation of metal catalysts is prevented, and their stability is improved in the porous carbon matrix [24]. In the past decade, noble metal (Au, Ag, and Pt)-loaded CSs have received extensive research attention owing to its unique morphology and potential as an electrocatalyst [25][26][27][28] in sensor fabrication [26]. Noble metals promote the diffusion of target molecules towards the active metal sites; however, they suffer from the drawbacks of low metal dispersion and metal leaching.…”
Section: Introductionmentioning
confidence: 99%